Dilema Karir dan Keluarga: Partisipasi Kerja Perempuan Menikah di Indonesia - Fajri; Bachtiar, Nasri; Kamarni, Neng (Jurnal Informatika Ekonomi Bisnis, 2025)
Women's participation in the workforce is crucial for driving economic growth. Empowering women economically is key to combating poverty by providing access to and control over resources needed to earn a sustainable and long-term livelihood. The data used in this research is sourced from the 2022 National Socioeconomic Survey published by the Indonesian Central Bureau of Statistics. The research approach is quantitative, with data analysis employing binary logistic regression. The results of the study indicate that the factors suspected to influence the labor force participation of married women in Indonesia have a significant overall effect. The variable of household size has a significant negative effect, meaning it tends to reduce the probability of married women participating in the labor market. Conversely, the variables of education, age, status, Family Hope Program, region, credit ownership, and motorbike ownership have significant positive effects, meaning they tend to increase the probability of married women participating in the labor market.